[PP.13.09] THE EFFECTS OF BAROREFLEX ACTIVATION THERAPY ON BLOOD PRESSURE AND SYMPATHETIC FUNCTION IN PATIENTS WITH REFRACTORY HYPERTENSION – THE RATIONALE AND DESIGN OF THE NORDIC BAT STUDY. (September 2016) - Gordin, D.; Elmula, F.E. Fadl; Andersson, B.; Gottsäter, A.; Kahan, T.; Viigimaa, M.; Kjeldsen, S.E.; Christensen, K. Lodberg; Olsen, M.H.; Tikkanen, I.
Abstract : Objective: Baroreflex activation therapy (BAT) modulates the autonomic nervous system to restore sympathovagal balance. The aim of this study is to explore the effects of BAT on hypertension in patients with refractory (true resistant) hypertension (RH). Design and method: This academic (independent of industry support) randomized, double-blind, 1:1 parallel-design clinical trial will include 100 patients with RH from six hypertension centers in the Nordic countries. A Barostim Neo® System will be implanted and after 1 month of stabilization patients will be randomized to either BAT for 16 months or continuous pharmacotherapy (BAT off) for 8 months followed by the BAT for 8 months (Figure). Blood and urine samples will be drawn and measures of arterial and cardiac function and structure, and of autonomic function will be performed at randomization, and after 8 and 16 months. Eligible patients will be 18–70 years and have a daytime systolic ambulatory blood pressure (ABMP) of 145 mmHg or more, and/or a daytime diastolic ABMP of 95 mmHg or more, after witnessed intake of antihypertensive treatment (including at least 3 antihypertensive drugs, preferably a diuretic), with no changes in medication for a minimum of 4 weeks prior to enrolment. Patients with secondary causes of hypertension, severe renal insufficiency, untreated sleep apnea, pregnancy, type 1 diabetes, alcohol/drug abuse, or psychiatric illnesses, other than sinus rhythm (controlled atrial fibrillation is not a contraindication), uncontrolled systolic heart failure, aortic stenosis, and a cardiovascular event 3 within months before enrolment will be excluded. Results: The primary end point is to test whether BAT reduces 24-hour systolic ABMP at 8 months of follow-up compared to pharmacotherapy. Secondary/tertiary endpoints are the effects of BAT on home and office blood pressure, measures of autonomic function, arterial and cardiac structure and function during follow-up, and extended long-term follow-up. Two patients have been included in the study so far. An interim analysis will be done after 50 patients. Conclusions: This initiative will increase the understanding of the mechanisms and role of BAT in the treatment of RH. Figure. No caption available.